The Impact of Disclosure on Diversity: Evidence From the Canada Business Corporations Act - Bourveau, Thomas; Gao, Xingchao; Hope, Ole‐Kristian (Contemporary Accounting Research, 2026)
ABSTRACT We examine the impact of a 2020 “comply‐or‐explain” disclosure mandate implemented in Canada. This regulation imposed the first disclosure mandate extending beyond gender diversity to include racial diversity. Using federally registered public firms as a treatment group and provincially registered public firms as a control group, we establish two main findings. First, racial diversity increased among directors of firms subject to the disclosure mandate. Gender diversity also increased, but only for firms not subject to an earlier rule pertaining only to gender diversity. Second, the impact of the disclosure mandate is plausibly driven by shareholder monitoring, notably through director elections. Overall, our findings contribute to the policy debate on the effects of disclosure mandates on social dimensions.